Study of the operating modes of the high voltage power source for barrier type discharge excitation - A. L. Barakhoev; O. I. Tikhon; V. V. Tuboltsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The issues related to the features of operation and modes setting of a high-voltage switching power source based on a sequential autonomous resonant inverter with reverse diodes used to excite an atmospheric pressure barrier type discharge are discussed in the article. It is indicated that the characteristic features of the autonomous resonant inverters operation are the occurrence of damped voltage fluctuations in the LC circuit of the inverter, as well as the dependence of the output alternating voltage on the ratio of the inverter operating frequency (thyristor switching frequency) to the natural resonant frequency of the LC circuit. Depending on this ratio, the inverter can operate in discontinuous, boundary and continuous current mode. The amplitude and shape of the inverter output voltage were controlled using a 1:1000 voltage divider with a C1-65A oscilloscope. The shape of the gate trigger pulses was obtained using a C1-167 oscilloscope. It is established that when the gate trigger pulses are asymmetrical relative to each other due to the operation features of the step-up transformers, the value of the alternating high-voltage at the inverter output is insufficient to excite the atmospheric pressure barrier type discharge. In the case of the gate trigger pulses symmetry, the output voltage of the inverter stage reaches the values required for the breakdown of the dielectric medium. Oscillograms of the inverter output voltage while adjusting its operating frequency are obtained. It is shown that the amplitude value of the voltage at the gas-discharge load increases as the operating frequency of the inverter increases. For the gate trigger pulses frequency of 250 Hz the value of the inverter output voltage amplitude was 3.4 kV, for 460 Hz – 4.0 kV, and for 550 Hz – 4.2 kV.